Association of oral health status with overweight and obesity in older adults aged ≥ 65 years- evidence from Chinese communities - Kan Wu; Wei yin; Xinhua Liang; Zheng Yang (BMC Public Health)
Abstract Objectives To evaluate the association of poor oral health conditions, such as caries, tooth loss, and tooth loss, with overweight and obesity in older adults and to complement evidence from the Chinese community to confirm this association. Additionally, we evaluated the sociodemographic characteristics, health status, and impact of health-related behavior on the BMI of older adults. Methods This retrospective study involved health examination and follow-up data of 953 older adults from the Sichuan Province of China from 2021 to 2023. The caries status assessed by the Decayed, Missing, and Filled Teeth (DMFT) index, was used as the exposure factor, whereas body mass index (BMI) was used as the outcome indicator. The influence of confounding variables, namely the sociodemographic characteristics, health status, and oral health-related behavior, was controlled. BMI changes in older adults with different levels of oral health over 3 years were retrospectively followed up. Additionally, a Cox proportional hazard model was used to determine the association. Results Overweight and obesity were prevalent in 29.3% and 20.4% of older adults with poor and good oral health status, respectively (P < 0.01). After controlling for the confounding factors, the Cox proportional hazards model demonstrated that the DMFT index was associated with overweight or obesity (BMI) (hazards ratio = 1.86, 95% confidence interval: 1.52–2.28). Overweight and obesity were less prevalent in older adults with fewer chronic diseases, higher frequency of physical exercise, and better oral health-related behaviors. Conclusions Oral health status is positively associated with overweight and obesity in older adults, particularly in older adults presenting with caries, missing teeth, and tooth loss as their primary symptoms.